Does Anemia Have a Potential Effect on Type 2 Hepatorenal Syndrome? - Sondes Bizid; Haythem Yacoub; Ghanem Mohamed; Bahaa Ben Slimane; Khouloud Boughoula; Hatem Ben Abdallah; Riadh Bouali; Nabil Abedelli (Canadian Journal of Gastroenterology and Hepatology, 2020)
Background/Aims. Hepatorenal syndrome (HRS) is a form of functional renal failure arising in advanced cirrhosis and is characterized by a poor survival rate. Anemia is frequently observed during the clinical course of cirrhosis. Our study aimed to investigate the hematologic findings in patients with cirrhosis to determine the effects of anemia on renal functions in type 2 HRS and if it was a potential aggravating factor. Materials and Methods. This prospective study, in which all consecutive patients with cirrhosis were enrolled, was performed at a tertiary-level hospital (Military Hospital of Tunis) from January 2019 to June 2019. A total of 9 patients with HRS fulfilled the type 2 HRS diagnostic criteria, and 41 patients with cirrhosis without HRS were included. All data regarding patients were obtained from the medical record. Demographic data, routine hemograms, biochemical, and urinary test results were collected. Models of end-stage liver disease (MELD) and Child–Turcotte–Pugh (CTP) scores were calculated. Results. The most common etiology of cirrhosis was viral hepatitis (66%). According to the CTP score, 23 patients were in the CTP-A stage, 13 in the CTP-B stage, and 14 patients were in the CTP-C stage. Patients with type 2 HRS had significantly lower hemoglobin levels compared with non-HRS stable cirrhosis patients. As hemoglobin levels decreased, renal function worsened on patients with type 2 HRS. Patients with lower hemoglobin levels had poor prognosis and survival compared with patients with higher hemoglobin levels. Logistic regression analysis showed that lower hemoglobin levels and higher MELD and CTP scores were statistically significant for an onset of type 2 HRS. Conclusion. Renal dysfunction is a frequent complication in patients with end-stage chronic liver disease. The role of anemia in aggravating HRS in patients with cirrhosis is explained by hypoxia that can lead to microcirculatory renal ischemia. Other studies are required to determine if anemia is a precipitant factor for HRS or not.